The Effect of Problem Based Learning Method in Reading Descriptive Text at the 10th Grade of Senior High School - Rosyidi, Ahmad Zuhri; Pratama, Anggun (Teaching English and Language Learning English Journal, 2024)
Problem Based Learning (PBL) is an instructional method in which students learn through solving problem and reflecting on their experiences. The statement of the problems of this research were: (1) Is Problem based learning method effective in teaching reading descriptive text at the 10th grade of SMA IT Dhiaul Fikri in the school year 2021-2022 (2) To what extent is the effect of Problem Based Learning method in reading descriptive text at the 10th grade of SMA IT Dhiaul Fikri in the school year 2021-2022. The purpose of this research is to know whether Problem Based Learning is effective in reading descriptive text at the tenth grade of SMA IT Dhiaul Fikri in the school year 2020-2021 and to know the extent of the effect of Problem Based Learning method in reading descriptive text at the tenth grades of SMA IT Dhiaul Fikri in the school year 2020-2021. This study used an experimental design. The population of the research was 30 students and the sample was 30 students from all of the population. In collecting data, the researcher used instrument to measure the effect of Problem Based Learning method on students’ reading descriptive text. To analyze the data, the researcher used paired-samples t-test. The result of data analysis that there was a significant difference in the scores between the pre-test and the post-test, t(df=29) = 5.203 at p = 0.000, meaning that the null hypothesis is rejected (Ho) and alternative hypothesis is accepted (Ha). It means that there was a significant effect of Problem based learning method on reading descriptive text for the tenth graders of SMA IT Dhiaul Fikri in the school year 2020-2021.